A Case of Recurrent Idiopathic Hypertrophic Pachymeningitis After Years of Quiescence. (5th December 2022) - Bird, Benjamin; Sheikh, Zahir; Zachariah, Jikku Jose
Abstract : Objective: To report a case of idiopathic hypertrophic pachymeningitis with recurrence in a new region of the brain after years of quiescence. Background: Idiopathic hypertrophic pachymeningitis (IHP) is a rare condition defined by thickening of the dural layer secondary to inflammation without discernible cause. Common symptoms include headache, cranial neuropathies, visual loss, mastoiditis and hearing loss. We present a case of a woman with two discrete episodes of headache and vision changes associated with dural thickening and parenchymal edema in separate locations, eventually with biopsy-supported diagnosis of IHP. A 41-year-old woman presented to our hospital with days of persistent temporal headache, blurred vision and confusion. MRI of the brain with contrast demonstrated left temporal lobe edema and overlying dural thickening, initially concerning for mastoiditis versus malignancy. Bloodwork revealed mildly elevated CRP and chronic untreated hepatitis C (HCV). Lumbar puncture was unrevealing, including cell counts, flow cytometry, cytology, cultures, CSF RPR and herpes simplex. Additional infectious workup, including for tuberculosis and fungi, was negative. IgG4 levels were normal, and ANCA screening was negative. CT of the chest revealed lung and liver nodules with non-specific inflammation on biopsy. Mastoidectomy with myringotomy showed no infection. PET scan was unremarkable. Ultimately, biopsy of dural thickening showed chronic inflammation, predominantly CD-163+ histiocytes without granulomas or malignancy. Seven years prior, the patient suffered a similar episode, with MRI showing extensive bilateral frontal dural thickening with associated edema. Symptoms resolved after course of corticosteroids with taper, though minor right frontopolar gliosis persisted. IHP suspected after similar workup, but no biopsy performed. Design/Methods: NA. Results: NA. Conclusions: IHP is clinically well-described, but data on course and recurrence patterns over time is scarce. This case demonstrates that recurrence is not restricted to original affected areas and can happen after years of quiescence. Given course and positive HCV, further longitudinal follow-up and studies are warranted.